Post-Divorce Experiences in Jordan: A Phenomenological Perspective - Alothman, Husein M.; Al-Hourani, Mohammed (Al-Adab Journal, 2018)
This study analyzes the post-divorce experiences of a sample of 50 Jordanian divorced participants. Qualitative and exploratory results are similar to the results of other studies that were conducted in certain western cultures. Similar issues included modern reasons for exiting a marriage, men's experiences of losing children and women's poor financial circumstances. Despite changes in the structure and function of the Jordanian family, post-divorce experiences continue to be influenced by the major factors of a traditional gender culture regarding the traditional reasons to exit marriage, with women retaining custody of children when they do not remarry and failure to establish cooperative custody. In addition, the results of this study reveal that progressive changes in women's choices to exit their marriages to better themselves. The study also sheds light on the perception of violence against married women as a reason for exiting marriage and family support to minimize the negative effects of divorce on women with a concurrent realization of the stigmatization of society toward divorced women. Nevertheless, additional research on this topic is needed to significantly add to our understanding of these phenomena